Oral Squamous Cell Carcinoma Arising in a Patient after Hematopoietic Stem Cell Transplantation with Bisphosphonate-Related Osteonecrosis of the Jaws - Paolo G. Arduino; Crispian Scully; Luigi Chiusa; Roberto Broccoletti (Case Reports in Dentistry)
A 55-year-old man with a history of acute myeloid leukaemia treated with hematopoietic stem cell transplantation and with a 5-year history of bisphosphonate-related osteonecrosis of the jaws, following 12 cycles of intravenous zoledronic acid therapy, presented in December 2009 with a history of increasingly severe unilateral lower jaw pain. Oral examination revealed, as previously, exposed bone in the left mandible, but also a new exophytic mass on the lower-left buccal mucosa. Biopsy confirmed a diagnosis of oral squamous cell carcinoma. To the best of our knowledge, this is the first report of an oral squamous cell carcinoma that appeared adjacent to an area of osteochemonecrosis.